A Qualitative Study of Challenges Faced by Cambodian Teachers in Implementing Student-Centered Approaches - Sokmuoy Samoun; Dina Pen (MASI Mandiri Edukasi, 2025)
This study aimed to explore the challenges faced by teachers of English in implementing student-centered approaches at the National University of Cheasim Kamchaymear (NUCK), Kampong Cham branch, the University of Heng Samrin Thbong Khmum (UHST), and Svay Rieng University (SRU). The research focused on the benefits, challenges, and potential solutions related to learner-centered instruction. A qualitative case study design was employed, and thematic analysis was used to interpret data collected from nine key participants through semi-structured interviews. The findings indicated that student-centered approaches enhance students' critical thinking skills, improve engagement and collaboration, build confidence and motivation, and foster learner autonomy. However, several significant challenges were identified, including mixed-ability students, time constraints, language barriers, entrenched learning habits, and cultural factors. Despite these obstacles, teachers proposed solutions such as professional development, flexible teaching methods, thoughtful student grouping, small and structured activities, and enhanced motivation and support. These findings offer practical guidance for teacher training programs and inform education policymakers seeking to promote more effective student-centered practices in Cambodian higher education.